Prophage-Dependent Neighbor Predation Fosters Horizontal Gene Transfer by Natural Transformation - Roberto C. Molina-Quiroz (American Society for Microbiology, 2020)
ABSTRACT Natural transformation is a broadly conserved mechanism of horizontal gene transfer (HGT) in bacteria that can shape their evolution through the acquisition of genes that promote virulence, antibiotic resistance, and other traits. Recent work has established that neighbor predation via type VI secretion systems, bacteriocins, and virulent phages plays an important role in promoting HGT. Here, we demonstrate that in chitin estuary microcosms, Vibrio cholerae K139 lysogens exhibit prophage-dependent neighbor predation of nonlysogens to enhance HGT. Through predation of nonlysogens, K139 lysogens also have a fitness advantage under these microcosm conditions. The ecological strategy revealed by our work provides a better understanding of the evolutionary mechanisms used by bacteria to adapt in their natural setting and contributes to our understanding of the selective pressures that may drive prophage maintenance in bacterial genomes. IMPORTANCE Prophages are nearly ubiquitous in bacterial species. These integrated phage elements have previously been implicated in horizontal gene transfer (HGT) largely through their ability to carry out transduction (generalized or specialized). Here, we show that prophage-encoded viral particles promote neighbor predation leading to enhanced HGT by natural transformation in the waterborne pathogen Vibrio cholerae. Our findings contribute to a comprehensive understanding of the dynamic forces involved in prophage maintenance which ultimately drive the evolution of naturally competent bacteria in their natural environment.